2008
DOI: 10.1071/ah080488
|View full text |Cite
|
Sign up to set email alerts
|

Did general practice health assessments of older Australians improve equity?

Abstract: Objective: To examine if claims for general practice health assessments of older persons in Australia over the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Our data supports observations that older women are more proactive in preventative health-seeking behaviour than men of the same age, as evidenced by the sex differential in the number of Medicarefunded health assessments (O'Halloran et al 2006;Byles et al 2007;Chan et al 2008), that remains even after 85 years of age (Gill et al 2008). In 2009-2010, our data shows that six states provided more than 15,000 services per 100,000 population (age standardised rate), except for NT and ACT.…”
Section: Comparison With Previous Researchsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data supports observations that older women are more proactive in preventative health-seeking behaviour than men of the same age, as evidenced by the sex differential in the number of Medicarefunded health assessments (O'Halloran et al 2006;Byles et al 2007;Chan et al 2008), that remains even after 85 years of age (Gill et al 2008). In 2009-2010, our data shows that six states provided more than 15,000 services per 100,000 population (age standardised rate), except for NT and ACT.…”
Section: Comparison With Previous Researchsupporting
confidence: 78%
“…Lack of awareness of the 75+ HA process itself may also contribute to low response rates or refusal to participate. A study revealed that close to 20% of older adults who had never undergone a 75+HA refused to participate (Chew et al 1994b), In contrast, patients who had undertaken the 75+HA perceived that it was beneficial to their wellbeing (Gill et al 2008;Spillman et al 2012) and that they were likely to repeat the assessment at a later date (Chew et al 1994b).…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…35 Unfortunately, a direct comparison with the non-indigenous population is not possible as a change in Medicare reimbursement categories after 2010 makes it difficult to identify the use of health assessments by people aged 75 years and over in the nonindigenous population. 34 …”
Section: Reorienting Primary Health Services To Address Aging In Austmentioning
confidence: 99%
“…33 The most disadvantaged populations have similar or higher levels of uptake of the extended primary care services in total (which include both chronic disease management plan services and the health assessments). 34 Overall though, only about one-fifth of the eligible population has received a health assessment.…”
Section: Reorienting Primary Health Services To Address Aging In Austmentioning
confidence: 99%
“…By September 2002, an estimated 31% of all eligible older Australians had at least one Medicare claim for a health assessment item. Health assessments were most likely to be used by women, aged 80–84 years, living in more urban and more economically advantaged areas and entitled to treatment under DVA arrangements . By 2003, four years after their introduction, 49% of eligible women in the 1921–1926 cohort of the Australian Longitudinal Study on Women's Health had received at least one assessment; however, few had repeat assessments.…”
mentioning
confidence: 99%